Hogyan kerültek kalotaszegi varrottasok a királylány kelengyéjébe? - Sarolta PÜSÖK (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
Why Are There Traditional Embroideries from Călata Region (Kalotaszeg) in the Dowry of a Princess?[1]